PREDIKSI PENINGKATAN KADAR HB PADA ANAK BAWAH TIGA TAHUN ANEMIA SETELAH MENDAPAT INTERVENSI ZAT BESI DI DESA PAGELARAN, CIOMAS, BOGOR - Sri Muljati; Astuti Lamid; Sudjasmin Sudjasmin; Basuki Budiman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2000)
PREDICTION OF HAEMOGLOBIN ELEVATION IN ANEMIA CHILDREN UNDER THREE YEARS AFTER IRON-INTERVENTION A STUDY FROM VILLAGE OF PAGELARAN SUB DISTRICT OF CIOMAS BOGOR.Background: Anenia is one of four nutrition problems in Indonesia. Impact of anemia in children 6-36 months (underthree children) related to their growth and development Program to combat the problem has been made, however data on the effect of such program on haemoglobin improvement are scarce.Objective: To elaborate the effects of oral iron 70 mg given weekly for four months intervention to children 6-36 months old whom suffers from anemia on changes of haemoglobin (Hb).Method: A four months follow up study on iron intervention to anemic children underthree years old had been carried out in the village of Pagelaran, Subdistrict of Ciomas, Bogor in 1999. The anemic children (<10 g%) screened from monthly weighing activity (POSYANDU). The parents consented to participate in tns study and allowed the author taken blood from finger tip of the children. A number of 58 out of 67 records had been performed. The rest dropped due to the uncompleted data; six children were believed not taken the all given iron and three children moved out the village. All children received 70 mg iron powder mixed with 40 mg Vitamin C and 40 mg Folic Acid weekly. Execution of this scheme was supervised every two weeks.Conclusions: There was improvement in haemoglobin level of the children 7-35 months of age after oral iron supplementation weekly for four months.Recommendations: To combat anemia in children 7-35 months of age, a weekly supplementation of iron as much as 70 mg together with 40 mg vitamin C and 40 mg folic acid is recommended as one of the alternative intervention.Key Words: haemoglobin, anemia, iron-intervention, underthree-years children